2020
DOI: 10.14295/bds.2020.v23i1.1893
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Composite Repair System to Bilayered Zirconia Using Different Surface Treatments (In Vitro Study)

Abstract: Objective:  the study is aimed to evaluate the effect of different surface treatment methods on shear bond strength between composite repair system and both of zirconia core and veneering porcelain and analyze the mode of failure between composite repair and ceramic surface. Material and methods: 40 Ceramic discs were fabricated with diameter of 7mm and 3mm thickness and divided according to material into two groups, Zirconia core discs (n = 20) and veneering porcelain discs (n = 20). Specimens were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although the ZLS group without crystallization presents higher values of µSBS, the ZLS group with additional crystallization has superior mechanical resistance, which can affect its clinical application [33]. Additionally, it is worth mentioning that only one aging method was employed, without other parameters for adhesive interface degradation such as mechanical fatigue [24], pH variation, biofilm formation, or surface treatment [37]. The samples were ideally treated, and there were no contaminants on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ZLS group without crystallization presents higher values of µSBS, the ZLS group with additional crystallization has superior mechanical resistance, which can affect its clinical application [33]. Additionally, it is worth mentioning that only one aging method was employed, without other parameters for adhesive interface degradation such as mechanical fatigue [24], pH variation, biofilm formation, or surface treatment [37]. The samples were ideally treated, and there were no contaminants on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study made by Polat, Tokar et al 2021 they reported the highest bond strength for 100% porcelain and mixed were in the control group with diamond bur with 16.76 MPa and 16.6 Mpa respectively. Baiomy et al 2020 , had four groups for surface treatment air abrasion, Cojet, Er,Cr:YSGG laser, and mixed group (Cojet and laser), in their study they revealed that there was a significant difference between the groups(SBS) highest bond strength was in Cojet group and the lowest value was in the laser group. These results are in accordance with a study made by Sarac et al 2013.…”
Section: Intraoral Repair Without Zirconia Exposurementioning
confidence: 99%
“…In the present study, direct composite veneers were applied on a core of BioHPP &PEKK with two different thicknesses. Resin composite material has many benefits when used as a veneering material, such as improving the esthetics of restorations made of opaque white polymers to a degree that could mimic the neighboring tooth structure, being less abrasive to natural teeth, being bio-compatible with surrounding tissues and could be easily repaired in clinics or labs [14].…”
Section: Introductionmentioning
confidence: 99%